Multisided Linear Induction Generator, Analytical Modeling, 3-D FEM Analysis and Experimental Tests - Hosseini Aliabadi, M.; Hosseinian, S. H.; Moghani, S. J.; Abedi, M. (Elektronika ir Elektrotechnika, 2013)
In this paper, a new generator for converting wave and tidal energy to electrical energy is proposed. At the beginning, analytical, 3-D FEM and 2-D FEM analysis have been developed and implemented on the dodecahedron tubular linear induction machine. The generator have been studied in normal weather condition in Persian Gulf and sensitivity analysis of the generator against sea wave period and height on the voltage, efficiency and thrust is studied. The results verify the accuracy of SETLIG model and show that tubular linear induction generator can be used as a powerful tool for converting wave energy to electrical energy. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2100